POSISIONING KEUNGGULAN MUTU LAYANAN UNIVERSITAS SWASTA MENGGUNAKAN UJI MULTIDIMENSIONAL SCALLING - sri Nugroho, Arif Julianto; Haris, Abdul; Marjukah, Anis; Setyawanti, Dandang; Tukiyo, Tukiyo; Tasari, Tasari (Surakarta Management Journal, 2024)
This research aims to conduct a perceptual mapping test of private universities in the Soloraya area based on student perceptions of service quality. The research object as samples was students at five universities, namely Unwidha, UMS, Muhammadiyah University of Klaten, Unisri and Unsa with a total of 100 respondents. The sampling technique was non-random purposive sampling. Service quality attributes tested in the research included brand image, quality of education, tuition fees, campus facilities, academic environment, and quality of teaching staff provided by a number of universities. The test activities carried out in the research included testing the validity and reliability of items as well as multidimensional scaling tests. The MDS test is useful in providing exposure to the perception map in the mind map of students at each university that is close to each other or farthest away based on the attribute of service quality excellence. The university position that appears in a perception map will show the excellent quality position of a university compared to other universities. Quantitative test of the perception map used SPSS 21 software. The research results found a map of the position of each university as an effort to develop a strategy to increase competitive excellence. UMS and Unisri are in a relatively excellent quadrant position compared to the other three universities. The beginning of research activities is to propose marketing strategy solutions to win competition among university institutions in the future